Side Lighting Enhances Morphophysiology by Inducing More Branching and Flowering in Chrysanthemum Grown in Controlled Environment - Jingli Yang (MDPI AG, 2021)
Light is one of the most important factors that influence plant growth and development. This study was conducted to examine how lighting direction affects plant morphophysiology by investigating plant growth parameters, leaf anatomy, epidermal cell elongation, stomatal properties, chloroplast arrangement, and physiological changes. In closed-type plant factory units, the rooted cuttings of two chrysanthemum (Chrysanthemum morifolium Ramat.) cultivars, ‘Gaya Glory’ and ‘Pearl Egg’, were subjected to a 10 h photoperiod with a 300 μmol∙m−2∙s−1 photosynthetic photon flux density (PPFD) provided by light-emitting diodes (LEDs) from three directions relative to the plant including the top, side, and bottom. Compared to the top or bottom lighting, the side lighting greatly enhanced the plant growth, improved the leaf internal structure and chloroplast arrangement, induced small stomata with a higher density, and promoted stomatal opening, which is associated with an increased stomatal conductance and photosynthetic efficiency. It is worth noting that the side lighting significantly enhanced the induction of branching and flowering for both cultivars., The plants grown with side lighting consistently exhibited the greatest physiological performance. We conclude that the lighting direction had a profound effect on the morphophysiological characteristics of chrysanthemum, and that side lighting dramatically promoted their growth and development, especially in their branching and flowering.